The Use of Folding Paper to Support Students’ Understanding of Summation and Subtraction - Sabina Ndiung; Emilianus Jehadus; Eliterius Sennen (Universitas Pendidikan Ganesha, 2021)
Fractions are part of mathematical material that is difficult for elementary school teachers to teach which results in students not being able to solve problems related to the concept and arithmetic operation of fractions. The aim of this study is to improve the learning outcomes and the activeness of students in computing the addition and subtraction of fractions using folding paper. This research is a class action research using the design of Kemmis & McTaggart. The subjects of this study included students in Grade V of three elementary schools, with a total of 170 research subjects. The data were collected by using test and observation techniques. The test instrument used was eight items in the form of descriptions to measure mathematics learning outcomes, while observations were made by the observer using observation sheets to measure student activity in learning using folding paper. The data analysis technique used is quantitative descriptive technique with a minimum of 85% classical completeness criteria with a score of 75 for learning outcomes and the activeness of students at least in the active category. Based on the implementation of two-cycle learning, the results show that the learning outcomes of students have improved from cycle I to cycle II, with criteria for completeness exceeding the permitted requirements. Similar to the student activeness data increased from the fairly active category in the first cycle to the very active category in the second cycle. Thus it can be said that the use of folding paper can enhance the students' activeness and learning outcomes in the computation of the addition and subtraction of fractions. So it is suggested that teachers as innovators have the awareness to innovate in material knowledge content and use teaching aids in learning.